1993
DOI: 10.1073/pnas.90.14.6825
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer disease A68 proteins injected into rat brain induce codeposits of beta-amyloid, ubiquitin, and alpha 1-antichymotrypsin.

Abstract: Aberrandy phosphorylated tau proteins (i.e., A68 or PHF-tau) and (-amyloid MATERIALS AND METHODS Isolation and Characterization of A68, Dephosphorylated A68 (DEP-A68), and Normal Tau. A68 was purified from the brains of four AD patients and one Down syndrome patient with . To render A68 water soluble for injection, A68 was further purified as follows. After sucrose gradient centrifugation (14,15), the 1.25-2.0 M and 2.25-2.5 M sucrose fractions were extracted in 2 M guanidine isothiocyanate at 37°C for 60 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 29 publications
3
30
0
1
Order By: Relevance
“…Five microliters of these A␤1-40 (10 g/ l) or A␤1-42 (10 g/ l) were injected into the right side of the hippocampus or deep cerebral cortex of female Sprague Dawley rats (200 -300 gm; n ϭ 50). After different postinjection survival times, the brains removed from the rats were fixed in 70% ethanol /0.15 M NaC l and embedded in paraffin as reported previously (Shin et al, 1993(Shin et al, , 1994. The postinjection survival times included 1 d (n ϭ 5), 1 week (n ϭ 5), 3 weeks (n ϭ 5), 5 weeks (n ϭ 5), and 7 weeks (n ϭ 5) for A␤1-40 as well as for A␤1-42.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five microliters of these A␤1-40 (10 g/ l) or A␤1-42 (10 g/ l) were injected into the right side of the hippocampus or deep cerebral cortex of female Sprague Dawley rats (200 -300 gm; n ϭ 50). After different postinjection survival times, the brains removed from the rats were fixed in 70% ethanol /0.15 M NaC l and embedded in paraffin as reported previously (Shin et al, 1993(Shin et al, , 1994. The postinjection survival times included 1 d (n ϭ 5), 1 week (n ϭ 5), 3 weeks (n ϭ 5), 5 weeks (n ϭ 5), and 7 weeks (n ϭ 5) for A␤1-40 as well as for A␤1-42.…”
Section: Methodsmentioning
confidence: 99%
“…After different postinjection survival times, the rats were perf used with PBS, followed by perf usion with 4% glutaraldehyde/0.1 M cachodylate buffer, pH 7.4, as described (Shin et al, 1993). The postinjection survival times included 1 week (n ϭ 8), 2 weeks (n ϭ 5), and 3 weeks (n ϭ 5).…”
Section: Methodsmentioning
confidence: 99%
“…The concept that AD Aβ pathology can be transmitted from injections of AD brain lysates was first demonstrated in primate by Baker et al ,130 131 but this could not be replicated with injections of purified AD PHF tau proteins into non-Tg rat brains 132. However, more recently it was shown that tau pathology can propagate in a cell to cell manner 32.…”
Section: Therapeutic Strategies For Tau Mediated Neurodegenerationmentioning
confidence: 99%
“…An early study on transmissibility of AD was performed on hamsters which were inoculated with a buffy coat preparation from AD patients [68]. These animals developed CJD-like histopathological alterations.…”
Section: Experimental Seeding Of Tau Protein Lead To Progression Of Pmentioning
confidence: 99%